Attitudes Toward Transgender People Among Medical Students in South Korea. Issue 1 (5th December 2020) - Lee, Sa Ra; Kim, Min-A; Choi, Mun Nyeong; Park, Suyeon; Cho, Jaehyun; Lee, Chulmin; Lee, Eun Sil
Abstract: Introduction: Interventions aimed at changing knowledge, attitudes, and beliefs of resident physicians and medical students have been made to incite a significant positive increase in attitudes, comfort, and knowledge toward the lesbian, gay, bisexual, and transgender (LGBT) community, as well as increased levels of competency among participants. Aim: To use insights from the attitudes of medical students toward transgender people and demonstrate that adding lectures on transgenderism would make the medical school curricula more comprehensive and trans-inclusive by improving overall attitudes toward the LGBT community. Methods: A total of 49 medical students completed the preintervention survey with the Genderism and Transphobia Scale and Attitudes Toward Transgendered Individuals Scale, and then took a class on transgenderism, whereas 39 individuals completed the 4-week postintervention survey following the same measures. Main Outcome Measure: Three items of survey were demographic characteristics, the Genderism and Transphobia Scale, and the Attitude Toward Transgender Individuals Scale. Results: Although there was no significant difference in mean score between the preintervention and postintervention surveys, those who had minority individuals as peers and those who had previous LGBT-related education showed significantly positive attitudes than those without after the lecture. As a result of analyzing all the data from the pre/postintervention surveys, being of the female gender and having minority individuals as peers positively affected attitude. Conclusion: Although there was no significant attitude change after the lecture, those who had previous LGBT-related education showed significantly positive attitudes at pre/postintervention surveys than those without. These findings suggest that raising awareness and education should be continued for a positive attitude toward more vulnerable groups such as the LGBT. Given the lack of studies on transgenderism that involve students in the medical profession in South Korea, this study shows the necessity of curricula creation of transgenderism education. This study aims to serve as a basis for curricula creation and student guidance that will help creating more positive attitudes toward sexual and gender minorities.